The Influence of Liquidity, Leverage, Profitability, and Operating Cash Flow on the Possibility of Financial Distress of PT. Waskita Karya (Persero) Tbk for the Period of 2014 – 2023 - Sonny Setyadhy; Yolanda Yolanda (Journal Of Social Science (JoSS), 2024)
This study aims to analyze the influence of liquidity, leverage, profitability, and operating cash flow on the possibility of financial distress at PT Waskita Karya (Persero) Tbk during the period of 2014-2023. Using multiple linear regression methods, this research processes financial data obtained from annual financial statements. The analysis results indicate that liquidity and leverage have a significant negative effect on the likelihood of financial distress, while profitability shows a significant positive effect. Operating cash flow does not demonstrate significant influence within this model. The research model has a fairly good explanatory capacity, with an adjusted R-squared of 63.73%. These findings suggest that effective working capital management and strategic use of debt can reduce the risk of financial distress; however, aggressive growth strategies reflected in high profitability increase that risk. This research provides insights into the financial dynamics within Indonesia's construction industry and can assist in formulating more effective risk management strategies.